Potential of Brewer's spent grain bioactive fractions as functional ingredients for companion and farm animal foods – A review - Emmanuel Duah Osei; Azza Silotry Naik; Gemma Kinsella; Terence Delaney; Stuart Kirwan (Applied Food Research, 2025)
Brewer's Spent Grain (BSG) is the primary by-product of the brewing industry, produced in large volumes. The improper disposal of BSG in landfills significantly contributes to CO₂ emissions, aggravating environmental challenges. To promote sustainability and foster a circular economy in the agri-food sector, BSG has been explored as a cost-effective and nutritionally rich ingredient for animal feed. However, this application is hindered by complexities including high perishability, low protein solubility, digestibility, and limited bioavailability. Recent studies highlighted the potential of BSG bioactive fractions (BBF) such as hydrolysates, as promising functional ingredients. BBF possesses a rich nutritional profile, improved digestibility, bioavailability, and techno-functional properties. They also demonstrate bioactivities, including antioxidant, antihypertensive, and antidiabetic effects. Despite these promising benefits, BBF applications in pet and animal food remain largely underexplored. This review examines the chemical composition of BSG, extraction of BSG bioactive fractions, their techno-functional properties, bioactivities, and potential applications as functional ingredients in pet and farm animal foods for improving general health and wellbeing.